2002
DOI: 10.1080/08037050211256
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NO Biosynthesis, but not Elevated Blood Pressure, Reduces Angiogenesis in Rat Models of Secondary Hypertension

Abstract: Arterial hypertension (AH) is characterized by reduced nitric oxide (NO) biosynthesis, vasoconstriction, and reduced microvascular density. In this study we asked whether AH also reduces the number of microvessels by impairing angiogenesis. AH was induced in Dahl salt-sensitive rats (DSS) with a salt diet and in Wistar-Kyoto rats by inhibiting NO formation with Nomega-nitro-L-arginine (NNA). Three weeks after induction of AH, two wound chambers containing collagen I (Vitrogen) were sutured into the mesenteric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
15
1
1
Order By: Relevance
“…Given these results, and the recent work of others examining the effects of chronic reductions in nitric oxide bioavailability on microvascular network structure (25,35,40,41), LZR were treated with L-NAME to investigate the effects of low nitric oxide bioavailability per se without the confounding influence of elevated oxidant stress on microvascular structure and function and skeletal muscle perfusion. Chronic inhibition of nitric oxide synthase did not impact any of the systemic measurements in LZR, with the singular exception of mean arterial pressure (abolished by concurrent treatment with hydralazine).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given these results, and the recent work of others examining the effects of chronic reductions in nitric oxide bioavailability on microvascular network structure (25,35,40,41), LZR were treated with L-NAME to investigate the effects of low nitric oxide bioavailability per se without the confounding influence of elevated oxidant stress on microvascular structure and function and skeletal muscle perfusion. Chronic inhibition of nitric oxide synthase did not impact any of the systemic measurements in LZR, with the singular exception of mean arterial pressure (abolished by concurrent treatment with hydralazine).…”
Section: Discussionmentioning
confidence: 98%
“…Taken together, these observations suggest that alterations to microvascular structure could play a major role in limiting skeletal muscle perfusion with increased metabolic demand in OZR. Given the observations that the insulinresistant condition, strongly present in OZR, causes a chronic reduction in the bioavailability of nitric oxide (23,33,53) and that previous studies examining mechanisms of angiogenic collateralization have suggested the central importance of nitric oxide bioavailability in the development of new microvessels (25,35,40,41), we hypothesized that chronic reductions in nitric oxide bioavailability, in part via oxidative radical scavenging (4,58), might contribute to structural alterations to microvascular networks in skeletal muscle of OZR, elevating vascular resistance and impairing functional hyperemic responses.…”
mentioning
confidence: 99%
“…Except ␤-blockers, all classes of antihypertensive drugs in present clinical use have demonstrated an ability both to impact on angiogenesis in specific nonhypertensive models and to influence microvascular rarefaction in experimental hypertension. 6,64 Three different calcium antagonists, nifedipine, verapamil, and nimodipine, have increased vascular density on the chick chorioallantoic membrane. 80 Calcium antagonists prevented myocardial capillary rarefaction in spontaneously hypertensive rats 37 and in 2 different models of secondary hypertension.…”
Section: Antihypertensive Treatment and Rarefactionmentioning
confidence: 99%
“…63 Impaired angiogenesis has been directly demonstrated in experimental hypertension induced by chronic pharmacological inhibition of NO synthesis. 64 There is no doubt that the renin-angiotensin system is implicated in angiogenesis but probably in a complex fashion involving an interplay of antagonistic and context-dependent influences (Figure). The complete picture is still lacking because of a high level of inconsistency in the literature.…”
Section: Mechanisms Of Rarefaction In Hypertensionmentioning
confidence: 99%
“…NO not only is a vasorelaxant but also is required for appropriate vascular budding in wound healing [33] and stimulates the expression of vascular growth factors, notably vascular VEGF [34]. Impaired angiogenesis has been directly demonstrated in experimental hypertension induced by chronic pharmacologic inhibition of NO synthesis [35].…”
Section: Capillary Rarefaction In Experimental and Human Hypertensionmentioning
confidence: 99%